Book Review: Transformation of Tradition: Islamic Law in Colonial Modernity, by Junaid Quadri, London, Oxford University Press, 2021, 265 pp., £22.53 (hardback), ISBN 978-01-90-077004-4 - Firmanda Taufiq; Muhammad Ahalla Tsauro (Indonesian Journal of Islamic Law, 2026)
This study examines the evolving discourse on colonial modernity and Islamic tradition through a focused analysis of Transformation of Tradition: Islamic Law in Colonial Modernity by Junaid Quadri. The work offers a detailed reading of the writings of Muḥammad Bakhīt al-Muṭīʿī, a prominent Azharī scholar and Grand Mufti of Egypt (1914–1920), with particular attention to his treatise Irshād Ahl al-Milla ilā Ithbāt al-Ahilla. By situating Bakhīt within the intellectual and institutional milieu of al-Azhar, the study traces his scholarly formation and engagement with the Hanafi juridical tradition. Through an exploration of the social, political, and cultural transformations associated with colonial modernity, the article argues that Bakhīt’s legal reasoning reflects significant departures from established Hanafi norms. The statement by Junaid Quadri in the book Transformation of Tradition: Islamic Law in Colonial Modernity is significant because it offers a new understanding of how Islamic law evolved during the colonial period, especially in Egypt. Rather than portraying Islamic legal scholars as merely passive victims of colonialism, Quadri demonstrates that Muslim scholars actively reinterpreted and reshaped Islamic legal traditions in response to changing political and social realities. Quadri’s analysis highlights how these shifts were not merely reactive but indicative of a broader reconfiguration of Islamic legal thought under colonial conditions. Ultimately, the study contributes to a deeper understanding of how colonial modernity exerted a powerful capacity for replication and expansion, reshaping the interpretive frameworks of the ulama and redefining the contours of Islamic legal tradition in the modern era.